Merton & Hesychasm: the prayer of the heart : the Eastern Church - Dieker, Bernadette; Montaldo, Jonathan (The Fons vitae Thomas Merton series, 2003)
The Fons Vitae Thomas Merton Series /Jonathan Montaldo, Gray Henry --Foreword: Merton and Hesychasm /Bernadette Dieker, Jonathan Montaldo --Hesychasm: The Gift of Eastern Christianity to Spiritual Practice --How Do We Enter the Heart, and What Do We Find When We Enter? /Kallistos Ware --Silence in Prayer: The Meaning of Hesychia /Kallistos Ware --The Power of the Name: The Jesus Prayer in Orthodox Spirituality /Kallistos Ware --The Ladder of Divine Ascent: The Yoga of Hesychasm /James Cutsinger --A Sufic Perspective on Saint Seraphim of Sarov /Gray Henry --Thomas Merton and Eastern Christianity --The Worship of the Whole Creation: Merton and the Eastern Fathers /A.M. Allchin --Our Lives, a Powerful Pentecost: Merton's Meeting with Russian Christianity /A.M. Allchin --Thomas Merton and the Christian East /John Eudes Bamberger --Thomas Merton and Byzantine Spirituality /M. Basil Pennington --Hesychasm /Patrick F. O'Connell --Heart /Patrick F. O'Connell --Bread in the Wilderness: The Monastic Ideal in Thomas Merton and Paul Evdokimov /Rowan Williams --Theophan the Recluse's Teaching on Prayer in Thomas Merton's Marginalia Throughout The Art of Prayer: An Orthodox Anthology /Jonathan Montaldo --Thomas Merton and the Silence of the Icons /Jim Forest --Merton and "Hagia Sophia" (Holy Wisdom) /Susan McCaslin --Hagia Sophia /Thomas Merton --Hesychasm in the Writing of Thomas Merton --The Climate of Monastic Prayer /Thomas Merton --The Wisdom of the Desert /Thomas Merton.